Use of natural coagulants for industrial wastewater treatment - S. Gautam; G. Saini (Global Journal of Environmental Science and Management)
Industrial effluents are a menace to the environment and the fact that their characteristics vary from industry-to-industry only adds to the complex challenge they offer to the engineers and scientists. Resource-efficient and environment-friendly solutions to this hazard are a call of the hour. Coagulation, by synthetic chemicals, has been used as a cost-effective and efficient method for managing the effluents generated by a large number of industries. However, the synthetic chemicals themselves are a cause of concern due to their non-native nature, non-degradability, and health conditions associated with their left-over residues. Natural coagulants offer a cost-effective, environment-friendly, and sustainable alternative to the application of synthetic chemicals. Such natural coagulants, despite their demonstrated effectiveness in treating the industrial wastewaters, have their own limitations and are yet to be investigated for large-scale applications. The current work presents a state-of-the-art review of the natural coagulants' application in treating industrial wastewaters and their relative advantages and disadvantages as compared to the chemical coagulants. Future research areas have also been identified that may ultimately lead to the large-scale commercial application of natural coagulants and will result in an environment-friendly and sustainable solution to the problems created by industrial effluents and synthetic chemical coagulants.